Interobserver variations of target volume delineation and its impact on irradiated volume in accelerated partial breast irradiation with intraoperative interstitial breast implant - Upreti, Ritu Raj; Budrukkar, Ashwini; Wadasadawala, Tabassum; Misra, Shagun; Gurram, Lavanya; Pathak, Rima; Deshpande, Deepak D. (Journal of Contemporary Brachytherapy, 2017)
Purpose: To investigate the interobserver variations in delineation of lumpectomy cavity (LC) and clinical target volume (CTV), and its impact on irradiated volume in accelerated partial breast irradiation using intraoperative multicatheter brachytherapy. Material and methods : Delineation of LC and CTV was done by five radiation oncologists on planning computed tomography (CT) scans of 20 patients with intraoperative interstitial breast implant. Cavity visualization index (CVI), four-point index ranging from (0 = poor) to (3 = excellent) was created and assigned by observers for each patient. In total, 200 contours for all observers and 100 treatment plans were evaluated. Spatial concordance (conformity index, CI common , and CIgen), average shift in the center of mass (COM), and ratio of maximum and minimum volumes (V max /V min ) of LC and CTV were quantified among all observers and statistically analyzed. Variation in active dwell positions (0.5 cm step) for each catheter, total reference air kerma (TRAK), volume enclosed by prescription isodose (V100%) among observers and its spatial concordance were analyzed. Results : The mean ± SD CI common of LC and CTV was 0.54 ± 0.09, and 0.58 ± 0.08, respectively. Conformity index tends to increase, shift in COM and V max /V min decrease significantly (p < 0.05), as CVI increased. Out of total 309 catheters, 29.8% catheters had no change, 29.8% and 17.5% catheters had variations of 1 and 2 dwell positions (0.5 cm and 1 cm), respectively. 9.3% catheters shown variations ≥ 10 dwell positions (5 cm). The mean ± SD CI common of V100% was 0.75 ± 0.11. The mean observed V max /V min of prescription isodose and TRAK was 1.18 (range, 1.03 to 1.56) and 1.11 (range, 1.03 to 1.35), respectively. Conclusions : Interobserver variability in delineation of target volume was found to be significantly related to CVI. Smaller variability was observed with excellent visualization of LC. Interobserver variations showed dosimetric impact on irradiation of breast tissue volume with prescription dose.